2017
DOI: 10.1371/journal.pone.0186293
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-4,5-bisphosphate is required for KCNQ1/KCNE1 channel function but not anterograde trafficking

Abstract: The slow delayed-rectifier potassium current (IKs) is crucial for human cardiac action potential repolarization. The formation of IKs requires co-assembly of the KCNQ1 α-subunit and KCNE1 β-subunit, and mutations in either of these subunits can lead to hereditary long QT syndrome types 1 and 5, respectively. It is widely recognised that the KCNQ1/KCNE1 (Q1/E1) channel requires phosphatidylinositol-4,5-bisphosphate (PIP2) binding for function. We previously identified a cluster of basic residues in the proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Positively charged amino acids have also been reported to facilitate ER export [42,43]. Thus the positively charged amino acids (K and R) in KSKRR or KSKR may be responsible for the forward trafficking of KCNE2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positively charged amino acids have also been reported to facilitate ER export [42,43]. Thus the positively charged amino acids (K and R) in KSKRR or KSKR may be responsible for the forward trafficking of KCNE2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we speculate that KCNE2 and KCNE1 are very likely to interact directly with the Sar1 through the [R/K](S)[R/K][R/K] motif presented at the C-terminus for ER export. It has also been suggested that the positively charged amino acids may associate with phospholipid components, which are present on the cellular membrane and involved in vesicle formation and trafficking [47], thus modulating ER export or plasmamembrane localization of membrane proteins [42,48]. Since the residues R67, K69, K70, and H73 in KCNE1 have been reported to be a key structural determinant of I Ks phosphatidylinositol 4,5-bisphosphate (PIP2) sensitivity [49], so it cannot be ruled out that the positively charged amino acids in the proximal C-terminus promote the ER export of KCNE1 and KCNE2 through binding to PIP2 or other phosphoinositide species.…”
Section: Discussionmentioning
confidence: 99%
“…Residues in the cytoplasmic domains of KCNQ1 have been shown to bind to other phospholipids 12 , 22 , 29 , 30 , including PI4P 12 , although consequences of the interactions with PI4P have not been explored. Recently, acute depletion of PI4P from the plasma membrane was shown not to affect KCNQ1/KCNE1 function 31 . In contrast to our results, the same study showed that prolonged depletion of membrane PI4P did not affect membrane expression using an N-terminus KCNE1 tagged construct fused to the KCNQ1 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…GFP-tagged constructs were fused with GFP at the C-terminus. Additional constructs used were Pseudojanin (PJ), a fusion protein of Sac and INPP5E phosphatase domains with FKBP (Addgene, #37999); PJ-Sac, a PJ based construct containing an inactivating mutation (Asp1263Ala) in the INPP5E domain (Addgene, #38000); PJ-INPP5E, a PJ based construct with an inactivating mutation (Cys779Ser) in the SAC1 domain (Addgene, #38001); PJ-DEAD, a PJ based construct containing an inactivating mutation (Asp1263Ala) in the INPP5E domain and an inactivating mutation (Cys779Ser) in the SAC1 domain (Addgene, #38002) 10 , 31 ; PH-PLCδ1-GFP (Addgene, #51407); LYN11-FRB-mcherry (Addgene, #38004); GFP-P4M-SidM (Addgene, #51469), hKCNH2-EGFP (VectorBuilder); EGFP-Kir2.1 (Addgene, #107184); Kv7.4-EGFP (Addgene, #111453); Kv2.1-EGFP (Addgene, #111531); constitutively active PI4K (Addgene, #139311); dominant negative PI4K-dead (Addgene, #139312); KCNE1-KCNQ1 tandem 33 . The adenoviral constructs hKCNQ1-GFP, hKCNE1 (Vector Biolabs) were used to infect rat ventricular cardiomyocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore it constitutes an alternative to the drastic osmotic shock produced by formamide to detubulate cells, interfering with the binding of the phospholipid to BAR domain-containing proteins (Suetsugu, Kurisu, & Takenawa, 2014). However, it is worth noticing that it may interfere with many cellular functions since PI(4,5)P 2 not only is crucial for membrane tubulation (Hofhuis et al, 2017;Inaba et al, 2016), but is an actor in endocytosis and exocytosis (Suetsugu et al, 2014), regulates ion channels (Royal, Tinker, & Harmer, 2017), and is involved in Ca 2+ signalling and intracellular pathways (Berridge, 2009). In ventricular myocytes, bridging integrator 1 (BIN1) is likely to interact with PI(4,5)P 2 because it contains a BAR domain and thus may allow the correct folding of the T-tubules and formation of the dyad (Fu et al, 2016;Hong et al, 2014).…”
Section: F I G U R E 4 Imipramine Affects Neither Cell Capacitance Nomentioning
confidence: 99%